\(-2y+y=6\)

\(-y=6\)

\(y=-6\)

substitute y into second equation \(4x-2y=5\)

\(4x-2(-6)=5\)

\(4x+12=5\)

\(4x=-7\)

\(\displaystyle{x}=-\frac{{7}}{{4}}\)

answer: \(\displaystyle{x}=-\frac{{7}}{{4}}\),

\(y=-6\)

Question

asked 2020-11-08

Radius of 8 , center at the intersection of \(x + 2y = 8\) and \(2x - 3y = -5\)

asked 2021-06-16

Solve the system by clennaton \(2x-y=0\)

\(3x-2y=-3\)

The solution is ( . )

asked 2021-01-31

asked 2021-06-12

a) \(2x + y = 11\)

\(x = 13 + y\)

b) \(2x = 11 - y\)

\(4x - y = 13\)

c) \(\displaystyle-\frac{{1}}{{2}}{x}-{y}=\frac{{3}}{{4}}\)

\(\displaystyle\frac{{3}}{{2}}{x}+{2}=-\frac{{7}}{{8}}\)

d) \(\displaystyle-{x}²+{y}={10}\)

\(x + y = 5\)